RESOLUTION OF DEMAK COASTAL CONFLICT - Dian Nafiatul Awaliyah (Jurnal Kolaborasi Resolusi Konflik, 2021)
ABSTRAKThe conflicts occur between economic interests by RTRW  (urban planning by regional government) which allow industrial expansion to run out of control, the interests of investors who exploiting the land without thinking of sustainability, thus violating land use, the characteristic factor of open access ownership, people's ignorance so that they change paddy fields into ponds so that they are not suitable for land use, people also over exploitative the groundwater which worsening the land subsidence. The conflict resolution very on different alternatives according to each party. The government advised the community to leave the submerged village but did not provide adequate facilities. The industry does not provide compensation for losses suffered by residents of villages next to the industrial area. Some environmentalists suggest that residents adapt to nature by building houses on stilts. Including pioneering spots along the coast in accordance with their respective local potentials, for example tourism, entrepreneurship, small and medium industries processing fish and other marine and coastal products, etc.